Glass beams reinforced with GFRP laminates: Experimental tests and numerical modelling using a discrete strong discontinuity approach. (15th September 2015) - Neto, P.; Alfaiate, J.; Valarinho, L.; Correia, J.R.; Branco, F.A.; Vinagre, J.
Highlights: Experimental and numerical investigations on glass–GFRP hybrid elements. Crack is embedded in the glass elements and modelled according to mode-I fracture. Glass–GFRP bond behaviour is defined under mode-II fracture. The elastic behaviour of the bond law is found to be determinant. A very good agreement between the numerical and experimental results is found. Abstract: This paper presents an experimental and numerical study about the bond behaviour between glass panes and glass fibre reinforced polymer (GFRP) laminates and the structural response of glass–GFRP beams. For this purpose, tests on glass–GFRP double-lap joints and tests on glass–GFRP hybrid beams were carried out. The finite element method was used and a discrete crack approach based on non-linear fracture mechanics was adopted. The bond between glass and GFRP is modelled by means of zero thickness interface elements. The material properties that characterize the interface, namely the shear stiffness, the cohesion and the mode-II fracture energy, are evaluated with the objective of simulating the experimental results obtained from double lap shear tests on glass–GFRP bonded joints. The obtained parameters, describing the bond-slip law between glass and GFRP, are then used to model the structural response of glass beams reinforced with GFRP. The numerical model is assessed by comparing the simulated structural responses and corresponding crack patterns with the experimental counterparts. This work contributes for a better understanding of the stress transfer mechanisms between glass and GFRP and the failure mechanisms found in the above-mentioned experimental tests, as well as to clarify the interpretation of the results obtained from those tests.